2000 Years of 'globes vs. maps' – lessons (to be) learned. Issue 2 (4th May 2018) - Hruby, Florian; Riedl, Andreas
ABSTRACT: This paper sheds light on the question of whether globes or maps are best suited to providing an adequate understanding of global phenomena. Drawing upon evidence from the history of cartography, we show how the ancient, medieval and early sixteenth-century mapmakers had already recognized the importance of globes and world maps. An analysis of Ptolemy, Strabo and the negotiations around the Treaty of Tordesillas will demonstrate how our basic assumptions regarding the relationships of globes and world maps have been present for a long time. These assumptions are discussed in the light of current user studies on world maps, for example on distance and area estimations and the issue of peripheral continuity. As we can see from this review of empirical research, designing an appropriate world map is not only an issue of map projection; the edge of a world map also affects the knowledge users may generate. In terms of the importance of 'globes vs. world maps', these findings indicate that globes are prominent because of their undistorted, but also seamless visualization of global phenomena.